CAD Software Evaluation for Product Design to Exchange Data in a Supply Chain Network - Zeki AyaÄŸ (International Journal of Supply Chain Management, 2015)
The sharing information in a supply chain environment, especially CAD models and drawings are so important companies. So, the selection of the most satisfying computer-aided design (CAD) software which enables to exchange data through supply chain network has been major issues for companies in a supply chain. The selection process of CAD software among the raising number of alternatives in the market has been very vital and critical issue for companies that aim to make their design and engineering related activities automated towards computer integrated manufacturing (CIM) environment. Therefore, most companies have used various methods to successfully carry out this difficult and time-consuming process. Of these methods, Analytic Hierarchy Process (AHP) has been widely used for Multiple Criteria Decision Making (MCDM) problems in both academic researches and practices. But, in some cases, due to the vagueness and uncertainty on judgments of the decision-maker(s), the crisp pair wise comparison in the conventional AHP seems to be insufficient and imprecise to capture the right judgments of decision-maker(s). Therefore, a fuzzy logic is introduced in the pair wise comparison of AHP to make up for this deficiency in the conventional AHP, called as fuzzy AHP. In this paper, a fuzzy AHP-based approach is proposed to evaluate a set of CAD software alternatives in the market to reach the best satisfying one based on the needs of company.